Consistency Between Celestial and Terrestrial Reference Frames and Earth Orientation Parameters: A Geodetic Perspective - Karbon, M. (2025)
The consistency between the International Celestial Reference Frame (ICRF), the International Terrestrial Reference Frame (ITRF), and Earth Orientation Parameters (EOPs) is essential for precise space geodesy and astronomy. While the ITRF and EOPs benefit from established multi-technique combination strategies, the current celestial realization, ICRF3, is based on independent catalogs at different frequencies and remains disconnected from the Gaia-CRF. Moreover, discrepancies among ITRF realizations (e.g., ITRF2020 and its update, DTRF2020, JTRF2020) due to differing combination strategies, and the aging IAU 2000/2006 Earth rotation models, further complicate the transformation between terrestrial and celestial systems. In this contribution, we assess systematic inconsistencies within and between these reference frames, examine the transparency and reliability of reported uncertainties in official geodetic products, and evaluate the impact of TRF choice on CRF determination. We also review recent recommendations for updating Earth rotation theory and IERS Conventions, highlighting the need for a harmonized framework that ensures mutual consistency among reference frames and EOPs, aligned with current precision requirements.